Preservation of cultural heritage through video documentation: A contemporary paradigm for preserving the socio-cultural tradition of the Kandyan dress - DE SILVA S. S. V; KARUNARATNE P. V. M; RANATHUNGA G. M (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The probability of preserving the Kandyan dress through video documentation is analyzed in this study. The research aims to shed light on the video documentation method as a practical means of preserving cultural heritage by discussing its benefits, challenges, hands-on approaches, and transcending methodology.Method: The data from this study will be analyzed qualitatively with the help of the literature review and theoretical frameworks.Findings: The Kandyan dress is created using a technique similar to sculpting, in which the fabric is shaped by pressure applied to the wearer’s body. This clothing is significant for anthropology and history because it reflects various social and economic factors and has a unique design.Implications/Novel Contribution: To better understand the potential and limitations of this practice and methodology, social scientists can use this application and overview.